Effects of Na+ Current and Mechanogated Channels in Myofibroblasts on Myocyte Excitability and Repolarization. (17th November 2016) - Zhan, Heqing; Zhang, Jingtao; Lin, Jialun; Han, Guilai
Abstract : Fibrotic remodeling, characterized by fibroblast phenotype switching, is often associated with atrial fibrillation and heart failure. This study aimed to investigate the effects on electrotonic myofibroblast-myocyte (Mfb-M) coupling on cardiac myocytes excitability and repolarization of the voltage-gated sodium channels (VGSCs) and single mechanogated channels (MGCs) in human atrial Mfbs. Mathematical modeling was developed from a combination of (1) models of the human atrial myocyte (including the stretch activated ion channel current, I S A C ) and Mfb and (2) our formulation of currents through VGSCs (I N a _ M f b ) and MGCs (I M G C _ M f b ) based upon experimental findings. The effects of changes in the intercellular coupling conductance, the number of coupled Mfbs, and the basic cycle length on the myocyte action potential were simulated. The results demonstrated that the integration ofI S A C, I N a _ M f b, andI M G C _ M f b reduced the amplitude of the myocyte membrane potential( V m a x ) and the action potential duration (APD), increased the depolarization of the resting myocyte membrane potential( V r e s t ), and made it easy to trigger spontaneous excitement in myocytes. For Mfbs, significant electrotonic depolarizations were exhibited with the addition ofI N a _ M f b andI M G C _ M f b . Our results indicated thatI S A C, I N a _ M f b, andI M G C _ M f b significantly influenced myocytes and Mfbs properties and should be considered in future cardiac pathological mathematical modeling.